The economic burden of kidney graft failure in the United States. Issue 5 (4th February 2020) - Sussell, Jesse; Silverstein, Alison R.; Goutam, Prodyumna; Incerti, Devin; Kee, Rebecca; Chen, Corinna X.; Batty, Donald S.; Jansen, Jeroen P.; Kasiske, Bertram L.
Abstract : Despite improvements in outcomes for kidney transplant recipients in the past decade, graft failure continues to impose substantial burden on patients. However, the population‐wide economic burden of graft failure has not been quantified. This study aims to fill that gap by comparing outcomes from a simulation model of kidney transplant patients in which patients are at risk for graft failure with an alternative simulation in which the risk of graft failure is assumed to be zero. Transitions through the model were estimated using Scientific Registry of Transplant Recipients data from 1987 to 2017. We estimated lifetime costs, overall survival, and quality‐adjusted life‐years (QALYs) for both scenarios and calculated the difference between them to obtain the burden of graft failure. We find that for the average patient, graft failure will impose additional medical costs of $78 079 (95% confidence interval [CI] $41 074, $112 409) and a loss of 1.66 QALYs (95% CI 1.15, 2.18). Given 17 644 kidney transplants in 2017, the total incremental lifetime medical costs associated with graft failure is $1.38B (95% CI $725M, $1.98B) and the total QALY loss is 29 289 (95% CI 20 291, 38 464). Efforts to reduce the incidence of graft failure or to mitigate its impact are urgently needed. Abstract : Using a state transition model to simulate the current kidney transplant patient experience in the United States and a counterfactual scenario in which graft failure does not occur, the authors find that for the 2017 kidney transplant cohort, graft failure is associated with incremental medical costs of $1.4B and 29, 000 lost quality‐adjusted life‐years.